Safety and efficacy of microwave endometrial ablation for patients with previous uterine surgery: a pilot study. (18th August 2022) - Maebayashi, Aki; Hayashi, Nobuki; Kamata, Saki; Sugi, Toshihiro; Nakajima, Takahiro; Nagaishi, Masaji; Kawana, Kei
Abstract: MEA (microwave endometrial ablation) is a treatment that can control hypermenorrhea. With the increase in the number of caesarean sections and myomectomies, an increasing number of patients with MEA have undergone previous incision of the uterine myometrium. Uterine perforation is major complication. Here we compared the incidence of complications and recurrence between groups with or without previous uterine surgery. 35 patients who underwent MEA were enrolled in the study. We assessed the thickness of uterine myometrium by MRI and transvaginal ultrasonography (TV-US). 12 patients (34%) had previous uterine surgery; Among 12 patients with previous uterine surgery, 6 (50%) showed thinning of the myometrium. No patient showed any complications. There was no difference in recurrence rate between two groups (1/12 = 8% and 2/23 = 8%, respectively). MEA can be performed safely and effectively even for patients with previous uterine surgery. IMPACT STATEMENT: What is already known on this subject? MEA (microwave endometrial ablation) is a treatment that can control hypermenorrhea.A few serious complications have been reported, including uterine perforation and intestinal injury. There have been no collective reports on women with a history of uterine surgery, and the decision to perform MEA and the detailed procedures have not been clarified. What do the results of this study add? No patient who received MEA showed any complication regardless of previous uterine surgery. There was no difference in recurrence rate of hypermenorrhea between groups with and without previous uterine surgery. MEA could be performed safely and effectively in patients with previous uterine surgery preoperative imaging and intraoperative ultrasounds What are the implications of these findings for clinical practice and/or further research? Curently, with the increase in the number of caesarean sections and myomectomies, the increasing number of patients with MEA have undergone previous incision of the uterine myometrium and this causes thinning of the myometrium. MEA can be safely performed without losing any therapeutic effect, even in patients with a history of uterine surgery, by using MRI and TV-US as preoperative evaluations.